Denny Sumargo's Partiality in the August 2025 Mass Demonstration Podcast: Corpus-Based Critical Discourse Analysis - Fitriyani Fitriyani; Asropah Asropah; Icuk Prayogi (Universitas Pahlawan Tuanku Tambusai, 2026)
The practice of language in digital media not only functions as a means of communication, but also represents ideology and power relations. This research aims to reveal Denny Sumargo's partiality in the YouTube podcast Curhat Bang episode